Modern anti-drug policy and human rights - Anatoliy Muzyka; Olexiy Gorokh; Lesya Muzyka; Oksana Muzyka-Stefanchuk; Mykhailo Anishchenko (Oñati Socio-Legal Series)
The topic of human rights in the aspect of relations between the state and addicted patients (and in general relations in the sphere of circulation of drugs) remains scantily explored for modern Ukraine, which actualizes further scientific research. The purpose of the article is to determine the authors’ vision of compliance with international human rights standards of the legal anti-drug prohibitions established by the state. To achieve this goal, using the historical-legal, comparative, dialectical, systemic, hermeneutic, sociological methods and legal method of cognition, national and foreign legislation was critically analyzed, international experience in implementing various models of anti-drug policy was studied, and proposals for the draft of a new Criminal Code of Ukraine were formulated. The authors pay special attention to the problems of protecting the rights of drug addicts, legal liability in the field of drug trafficking, legalization of drugs for non-medical needs and compulsory treatment of drug addicts.